Benefits and Drawbacks of Financial Reporting Practices: A Case Study of UD Harapan Jaya in Pallangga Village - Lestari, Putri Ayu (Yayasan Sinergi Kawula Muda, 2025)
Financial reporting is crucial for the sustainability and competitiveness of Micro, Small, and Medium Enterprises (MSMEs), yet many businesses in developing countries continue to rely on informal financial management practices. This study investigates the perceived benefits and barriers to financial reporting at UD Harapan Jaya, a construction material trading MSME in South Sulawesi, Indonesia. Employing a qualitative descriptive case study approach, data were collected through interviews and observations with the business owner and key staff. Thematic analysis was used to analyze the data and identify key patterns in financial practices and decision-making behaviors. Findings reveal that UD Harapan Jaya has yet to adopt formal financial reporting systems, relying instead on manual bookkeeping and intuitive decision-making. This has resulted in inefficiencies in cash flow management, limited access to financing, and weakened strategic planning. The study identifies significant internal barriers, including limited financial literacy and resource constraints, alongside external pressures such as market competition and fluctuating material prices. The research also highlights the potential of digital financial applications and government support programs in addressing these challenges, emphasizing their role in enhancing financial literacy and enabling MSMEs to transition toward structured reporting practices. The use of SWOT analysis and IFAS/EFAS matrices provided strategic insights that can inform actionable financial management improvements. These findings contribute to the literature on MSME financial practices in resource-constrained settings and suggest pathways for policy and practice interventions.